2004
DOI: 10.1093/nar/gkh884
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial tRNA 3' end metabolism and human disease

Abstract: Over 150 mutations in the mitochondrial genome have been shown to be associated with human disease. Remarkably, two-thirds of them are found in tRNA genes, which constitute only one-tenth of the mitochondrial genome. A total of 22 tRNAs punctuate the genome and are produced together with 11 mRNAs and 2 rRNAs from long polycistronic primary transcripts with almost no spacers. Pre-tRNAs thus require precise endonucleolytic excision. Furthermore, the CCA triplet which forms the 3' end of all tRNAs is not encoded,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
131
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(140 citation statements)
references
References 96 publications
4
131
0
1
Order By: Relevance
“…Thus, the mutated polypeptide may retain a partial function. Alternatively, the G7444A mutation is adjacent to the site of 3' end endonucleolytic processing of the L-strand RNA precursor, spanning tRNA Ser(UCN) and ND6 mRNA [Guan et al, 1998;Levinger et al, 2004]. Our previous data showed that the A7445G mutation in the precursor of tRNA Ser(UCN) led to a failure in the processing of the L-strand RNA precursor, thereby causing a marked decrease of the steady-state levels of tRNA Ser(UCN) and ND6 mRNA [Guan et al, 1998;Li et al, 2005b].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the mutated polypeptide may retain a partial function. Alternatively, the G7444A mutation is adjacent to the site of 3' end endonucleolytic processing of the L-strand RNA precursor, spanning tRNA Ser(UCN) and ND6 mRNA [Guan et al, 1998;Levinger et al, 2004]. Our previous data showed that the A7445G mutation in the precursor of tRNA Ser(UCN) led to a failure in the processing of the L-strand RNA precursor, thereby causing a marked decrease of the steady-state levels of tRNA Ser(UCN) and ND6 mRNA [Guan et al, 1998;Li et al, 2005b].…”
Section: Discussionmentioning
confidence: 99%
“…This processing, which is known as the RNA punctuation model (Ojala et al, 1980), is mediated by RNase P and tRNase Z endonucleases, respectively (Levinger et al, 2004). When multiple tRNA genes are present, as between nad3 and nad5…”
Section: Transcriptomementioning
confidence: 99%
“…Processing of mitochondrial pre-tRNA Ser(UCN) with tRNase Z S was also optimal with 2.5 mM CaCl 2 and could not be detected with Mn 2ϩ alone or in a mixture with Ca 2ϩ . In vitro pre-tRNA processing of unmodified transcripts has both advantages and limitations (4). The endonucleolytic end processing reactions may precede most of the nucleoside modifications; even so, the absence of the post-transcriptional nucleoside modifications in tRNA Ser(UCN) (e.g.…”
Section: Baculovirus Expression Of Human Trnase Zmentioning
confidence: 99%
“…The circular 16,568-base pair human mitochondrial genome (1) is bidirectionally transcribed into long polycistronic heavy (H) 4 -and light (L)-strand precursor RNAs. Two rRNAs and 11 mRNAs encoding 13 polypeptides (all of them subunits of complexes in the respiratory transport chain) are punctuated by 22 tRNAs (1 tRNA for each of 18 amino acids and 2 each for leucine and serine with different anticodons) with very little intergenic RNA (2,3).…”
mentioning
confidence: 99%
See 1 more Smart Citation